The World Book encyclopedia. (World Book, a Scott Fetzer Company, 2015)
A 22-volume, highly illustrated, A-Z general encyclopedia for all ages, featuring sections on how to use World Book, other research aids, pronunciation key, a student guide to better writing, speaking, and research skills, and comprehensive index--